The Effects of Experimental Left Varicocele on the Epididymis - Öztürk, U.; Kefeli, M.; Aşçi, R.; Akpolat, I.; Büyükalpelli, R.; Sarikaya, S. (Informa Healthcare, 2008)
Most of the studies investigating the relationship between varicocele and male infertility are mainly focused on the testicles. It is obvious that varicocele would affect the morphology and function of the epididymis which is an intrascrotal organ. In this study, the effects of experimental left varicocele (ELV) on the epididymal morphology were investigated in adult rats. ELV was induced via partial obstruction of the left renal vein in 20 Sprague-Dawley adult rats. An additional twelve rats served as controls, and another twelve served as shams. Half of the rats in the groups were sacrified by the end of the first month of the experiment, and the rest were sacrified by the end of the second month. Epididymides were weighed; tubular diameters of the caput, corpus, and cauda of the epididymis were measured. The TUNEL assay was used to assess apoptosis within the epididymal tubules. The mean weight of each right and left epididymis in the varicocele group was lower than that in the control and sham groups (p < 0.01). In the varicocele group, the left epididymis weighted less than the right by the end of the second month (p < 0.01). The mean tubular diameter in the varicocele group was narrower than that in the control and sham groups (p < 0.001). Tubular diameter was significantly narrower in the caput segments in rats with varicocele by the end of the second month (p < 0.001). Apoptosis was significantly increased in principal cells of the epididymal epithelium in the varicocele groups. The apoptotic cells in the caput epididymis epithelium were more numerous than those in the other segments. In conclusion, ELV significantly decreases epididymal weight and tubular diameters presenting increased apoptosis within the principal cells. There is a positive correlation between the epididymal damage and the duration of varicocele. Copyright © Informa Healthcare USA, Inc.
Keywords: Apoptosis; Epididymis; Experimental Varicocele; Histopathology; Rats